2000
DOI: 10.1111/j.1095-8312.2000.tb01230.x
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific diversity of mitochondrial DNA in the land snail Euhadra peliomphala (Bradybaenidae)

Abstract: Exceptionally high levels of intraspecific variation of mitochondrial DNA (mtDNA) sequences encoding 16s ribosoinal RNA (16SrRNA) lvere detected in populations of the land snail Euhadra pdiomplinla from the eastern part of Japan. Geographical isolation has occurred within small areas and has created many genetically distinct local populations. These are morphologically segregated into two cgroups: the first consists of populations from the southern part of the Izu Peninsula. and thr second of populations from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 13 publications
1
27
0
4
Order By: Relevance
“…These hypotheses are: (i) mtDNA evolution in pulmonates is exceptionally fast, (ii) haplotypes differentiate in isolated ‘refuges’ and subsequently come together, (iii) natural selection is acting to preserve variation, and (iv) the population structure of pulmonates favors the persistence of ancient haplotypes. The accelerated mtDNA evolution hypothesis was supported by the findings in some taxa [24], [26], [27], [28], but not in others [29], [30], [31], whereas a hypothesis was formulated, on developmental grounds, to account for the extraordinary mtDNA diversity in mollusks [32]. At the same time, several studies concluded that a history of allopatric divergence followed by secondary contact (hypothesis ii) could explain sympatry of diverse haplotypes [24], 30,31,33,34,35,36.…”
Section: Introductionmentioning
confidence: 69%
“…These hypotheses are: (i) mtDNA evolution in pulmonates is exceptionally fast, (ii) haplotypes differentiate in isolated ‘refuges’ and subsequently come together, (iii) natural selection is acting to preserve variation, and (iv) the population structure of pulmonates favors the persistence of ancient haplotypes. The accelerated mtDNA evolution hypothesis was supported by the findings in some taxa [24], [26], [27], [28], but not in others [29], [30], [31], whereas a hypothesis was formulated, on developmental grounds, to account for the extraordinary mtDNA diversity in mollusks [32]. At the same time, several studies concluded that a history of allopatric divergence followed by secondary contact (hypothesis ii) could explain sympatry of diverse haplotypes [24], 30,31,33,34,35,36.…”
Section: Introductionmentioning
confidence: 69%
“…This estimate has been used in recent terrestrial gastropod phylogenetic studies, including the New Zealand Paryphantinae (Spencer et al 2006). However, other researchers have claimed that much higher substitution rates exist within land snails, ranging up to 10-25% per million years (Chiba 1999, Hayashi & Chiba 2000, Thacker & Hadfield 2000, Watanabe & Chiba 2001, Haase et al 2003, Gittenberger et al 2004, Van Riehl et al 2005). While critical analysis of these claims is well beyond the scope of this contribution, we do note that rate estimation in all of these papers is not based on the fossil record but rather on inferred formation times of given biogeographic barriers.…”
Section: Discussionmentioning
confidence: 99%
“…The distributions of four species are shown in Figure 2, using data compiled from [50,51] and the Web site http://www.biodic.go.jp/site_map/site_map.html (in Japanese). We were also able to use an extensive set of 16S rRNA sequences from E. peliomphala [52]) and E. quaesita [33]. For the outgroup, Nesiohelix bipyramidalis was used because a prior analysis has suggested that it is suitable [31].…”
Section: Methodsmentioning
confidence: 99%